E-Museum Prototype Innovation for Edu Tourism Development Based on Smart Digital Android Application - Muhamad Nur Rokhman; Asyhar Basyari; Alifi Nur Prasetia Nugroho; Tio Anggara (ISTORIA : Jurnal Pendidikan dan Ilmu Sejarah, 2025)
The museum is one of the educational tourism objects (edu-tourism). Museums are usually used as a learning tool for the community. The great potential of museums as a means of education and tourism is less known by the public because there is no integrated information system related to museum information. One of the innovations that can attract the public is the development of Android-based e-museum applications. With the android-based e-museum application, the public can find out the specifications of each museum so that they can receive information according to their needs. Specifications of each museum so they can receive information according to visitor needs. This research aims to Innovate the development of museums based on information technology and develop the museum's potential as an educational tour. Digital website development uses the Research and Development (RnD) research method with the ADDIE model development steps. The ADDIE model consists of five steps, namely: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. The result of this research is the creation of an E-Museum prototype with a website platform with expert feasibility results (product validation) with the results of the media expert'sexpert's assessment of 4.35 (feasible) and the material expert'sexpert's assessment of 4.25 (very feasible). The results of the final evaluation of the product as a whole with the average value of the total score show a value of 4.3, so it can be concluded that the media developed is "very feasible" from the aspect of user assessment.